The Effectiveness of Regulatory Frameworks and Participatory Transparency Approaches in Village Fund Corruption Eradication within Regional Autonomy - Junet Hariyo Setiawan; Irwan Sapta Putra; Abdul Rafay (Corruptio, 2025)
Village fund corruption remains a critical issue within Indonesia’s decentralized governance system. Although Law No. 6 of 2014 on Villages and Law No. 23 of 2014 on Regional Government establish frameworks for transparency and accountability, their implementation has not effectively curbed corrupt practices. This study analyzes the effectiveness of these regulations in preventing village fund corruption and proposes legal strategies to enhance oversight. Using a normative juridical approach supported by empirical data from Indonesia Corruption Watch (ICW), the research finds that weak vertical supervision by the Regional Inspectorate, limited community participation, and inadequate administrative capacity among village officials undermine regulatory effectiveness. To address these challenges, the study recommends strengthening participatory audits, adopting context-appropriate digital transparency tools, reforming the institutional role of the Village Consultative Body (BPD), and enforcing stricter legal sanctions. A comprehensive and participatory legal approach is essential to reduce corruption and promote sustainable rural governance.